Vulnerability of vascular endothelium in lipopolysaccharide toxicity: effect of (acyl) carnitine on endothelial stability - W. C. Hülsmann (Hindawi Limited, 1993)
The literature presented illustrates that lipopolysaccharide (LPS), from bacterial cell walls, induces tumour necrosis factor (TNF) synthesis in macrophages. TNF affects a number of cell types, amongst which are endothelial cells, within a few hours. Its injection has been shown to produce all symptoms of the toxic syndrome. In the present communication the vulnerability of endothelial cells will be stressed. These cells require carnitine not only for fatty acid oxidation but also for membrane protection and repair. As endothelial cells lose carnitine during hypoperfusion, it is speculated that the supply of carnitine during the early phase of LPS toxicity in rats might delay or avoid loss of endothelial functions. Earlier it was observed that hearts from rats, injected 3 h previously with LPS, showed strongly increased interstitial fluid production compared to hearts from control rats, even when TNF was present during a 3 h in vitro perfusion. It showed that LPS in vivo generates factors other than TNF, such as platelet activating factor (PAF), that are responsible for the increased capillary permeability.